Prosesi Ijab Dan Kabul Via Telepon Ditinjau Dari Kaca Mata Ushul Fiqih Dan Qowaid Fiqhiyyah - Ulva Hiliyatur Rosida (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2022)
Marriage is a sunnatullah that applies to all creatures of Allah subhaanahu wa ta'ala. Everything created by Allah is paired and matched. The purpose of marriage according to Islamic law is to fulfill religious teachings and instructions to create a harmonious, happy and prosperous family. The purpose of this scientific work is to find out the purpose of the Ijab and Kabul processions via telephone and also to find out the Ijab and Kabul processions via telephone when viewed from the perspective of ushul fiqh and qawaidh fiqhiyyah. Marriage by telephone is a problem of contemporary Islamic law that did not exist in classical times. Ijab and Kabul are part of the marriage contract procession. Ijab is a pronunciation made by the woman, who is usually her guardian or deputy guardian. Kabul is the pronunciation made by the groom or groom. The Ijab and Kabul processions via telephone when viewed from the perspective of ushul fiqh can use the method or approach of maslahah mursalah and sad dzaria'ah. If viewed from the perspective of qawaidh fiqhiyyah is to use the rules of al-masyaqqah tajlib at-taysir. This research is a literature study whose materials are taken from books and scientific journal articles